Identification of conserved subdominant HIV Type 1 CD8(+) T Cell epitopes restricted within common HLA Supertypes for therapeutic HIV Type 1 vaccines. - Karlsson, I; Kløverpris, H; Jensen, K; Stryhn, A; Buus, S; Karlsson, A; Vinner, L; Goulder, P; Fomsgaard, A (2012)
The high HIV-1 prevalence, up to 4.6% in Guinea-Bissau, West Africa, makes it a relevant location for testing of therapeutic vaccines. With the aim of performing a clinical study in Guinea-Bissau, after first testing the vaccine for safety in Denmark, Europe, we here describe the design of a universal epitope peptide-based T cell vaccine with relevance for any geographic locations. The two major obstacles when designing such a vaccine are the high diversities of the HIV-1 genome and of the human major histocompatibility complex (MHC) class I. We selected 15 CD8-restricted epitopes predicted from conserved regions of HIV-1 that were subdominant (i.e., infrequently targeted) within natural infections. Moreover, the epitopes were predicted to be restricted to at least one of the five common HLA supertypes (HLA-A01, A02, A03, B07, and B44). Here, we validated the resulting peptide-specific, HLA-restricted T cell specificities using peptide-MHC class I tetramer labeling of CD8(+) T cells from HIV-1-infected individuals. The selected vaccine epitopes are infrequently targeted in HIV-1-infected individuals from both locations. Moreover, we HLA-typed HIV-1-infected individuals and demonstrated that the selected vaccine epitopes, when targeted, are restricted to the five most common HLA supertypes at both locations. Thus, the HLA supertype-directed approach achieved HLA coverage of 95% and 100% of the examined cohorts in Guinea-Bissau and Denmark, respectively. In conclusion, the selected vaccine epitopes match the host populations and HIV-1 strains of these two distant geographic regions, justifying clinical testing in both locations.